Preparation, Characterization And Properties Of Multiwalled Carbon Nanotube-Alumina Hybrid Nanocomposites - Abdul Kudus, Muhammad Helmi (2012)
This work focuses on synthesis of multi walled carbon nanotubes (MWCNT)-alumina hybrid compound via methane decomposition process using nickel catalyst and study on the preparation and properties of MWCNT-alumina hybrid epoxy composite.